1980
DOI: 10.1037/h0081079
|View full text |Cite
|
Sign up to set email alerts
|

Motives and attitudes of rapists.

Abstract: The current reformulation of the Canadian legal definition of rape proposes that rape is an act of assault (i.e., motivated by aggression). Psychological literature has, until recently, considered rape a sex act and has assumed that the motivation of rapists is sexual in nature. This paper reviews the rape literature in terms of such "motivations," and an overview shows that the attribution of motives has resulted in unnecessary confusion and contradictions. Studies based on non-motivational premises (i.e., at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…If they are stereotypic in the classic psychological sense, what is it that characterizes them as mythological, a term that generally implies a certain cultural function? Other definitions have also been proposed in the literature, and although they share the same connotations, there is significant variation among them (e.g., Briere, Malamuth, & Check, 1985;Hegeman & Meikle, 1980). This variation has important implications for the theoretical bases and development of measurement instruments in this field.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If they are stereotypic in the classic psychological sense, what is it that characterizes them as mythological, a term that generally implies a certain cultural function? Other definitions have also been proposed in the literature, and although they share the same connotations, there is significant variation among them (e.g., Briere, Malamuth, & Check, 1985;Hegeman & Meikle, 1980). This variation has important implications for the theoretical bases and development of measurement instruments in this field.…”
Section: Definitionsmentioning
confidence: 99%
“…Given that the prevalence of victimization for women has been estimated as high as 25 % (Brownmiller, 1975;Warshaw, 1988), it is not reasonable to suggest that any particular kind of woman is excluded from the threat of rape. It appears that numerous situational variables differentiate groups of women who experienced different levels of sexual victimization: "the relationship of the victim and offender, the violence of the assault, the resistance of the victim, emotional response of the victim, and sexual history of the victim" (Koss, 1985, p. 201).3 However, research has identified only three discriminating personal characteristics of rape survivors: youth, levels of sexual experience, and previous sexual abuse (Hegeman & Meikle, 1980;KOSS, 1985;Koss & Dinero, 1989;Russell, 1984). Although there may be a statistical "kernel of truth" to myths that younger, "sexually loose" women are more likely to be sexually assaulted, their status as myths rests on their emphasis, exaggeration, and most importantly, possible function.…”
Section: Definitionsmentioning
confidence: 99%
“…When rape was understood to be sexually motivated, the victim’s sexual history was viewed as relevant (Hegeman & Meikle, 1980). A focus on the sexuality of the victim subsequently led to the adoption of laws that increasingly dissected the victim’s sexual history in the press and the courtroom, required physical evidence of penetration and force, and the need for corroboration of her story by a witness (Bevacqua, 2000).…”
Section: History Of Theorizing Rapementioning
confidence: 99%
“…The dominance motivation perspective of rape has garnered much theoretical support (e.g., Brownmiller, 1975;Chiroro et al, 2004;Hazelwood & Burgess, 1987;Hegeman & Meikle, 1980;Jansssen, 1995;Lisak & Roth, 1990;McCabe & Wauchope, 2005;Russell, 1982;Sanday, 1981;Schwendinger & Schwendinger, 1974). It also has received empirical support (see Aosved & Long, 2006;Locke & Mahalik, 2005;Zurbriggen & Yost, 2004; also see Lisak & Roth, 1990;Muehlenhard & Falcon, 1990;Muir, Lonsway, & Payne, 1996).…”
Section: Motivations To Rapementioning
confidence: 99%